Does financing structure affects bank liquidity risk? - Abdul-Rahman, Aisyah; Sulaiman, Ahmad Azam; Mohd Said, Noor Latifah Hanim (Elsevier, 2018)
This paper investigates whether FS affects bank liquidity risk. Using the Malaysian banking data sets, we compare the FS-liquidity risk relationships between the Islamic and conventional banking institutions. FSs are measured by real estate financing, financing concentration, short-term FS stability, and finally medium-term FS stability. Meanwhile, for liquidity risk measures, we adopt the BASEL III approach such as liquidity coverage ratio (LCR) and the net stable funding ratio (NSFR) in quantifying short- and long-term liquidity risk, respectively. The unbalanced static panel regressions of 27 conventional and 17 Islamic banks from 1994 to 2014 were analyzed to evaluate the relationships. Our results illustrate that increasing number of real estate financing and short-term FS stability of the Islamic banks may increase both their short- and long-term liquidity risks. On the other hand, even though real estate financing does not affect liquidity risks of the conventional banks, increasing short-term FS stability and financing specialization may increase their long-term liquidity risk. As the liquidity risk behavior, to some extent, differs between the two banking systems, we recommend the regulatory bodies and market players to develop a separate liquidity risk management framework for conventional and Islamic banking institutions.